(untitled) (Eurasian Research Bulletin, 2022)
This work is devoted to the main issues of statistical analysis of clinical trials. Statistical processing is a complex multi-stage process, the level of scientific organization of which decisively determines the quality of the accumulated statistical data, the results of their processing and comprehension.